Digitalisasi Makam Penyiar Islam Raden Mas Suryodilogo di Pamboang Sulawesi Barat - Adawiah, Rabiatul; Hasyim Ashari; Ahmad Muaffaq; Husna; Nasrah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
Unlike the tombs of other Islamic broadcasters, the tomb of Raden Mas Suryodilogo has not received good attentions from the government and the public. The main purpose of this community service is to publish this historical site through digitization in the form of making a video and an infographic poster. This project is implemented from February to July 2022 using the Asset-based Community Development (ABCD) approach which emphasizes a community-driven element. The service team has carried out eight stages starting from team formation, training of trainers, appreciation interviews, asset mapping, observation and literature studies, FGD, making videos and posters, socialization to monitoring, and evaluation. In general, societies in Pamboang realize that they have assets and potential including religious tourism in the form of relics of Raden Mas Suryodilogo so the team did not find any obstacles when mapping assets. The community is also actively involved and willing to participate at the time of image taking and to disseminate information through the output of this PkM. ==== Berbeda dengan makam tokoh penyiar Islam lainnya, makam Raden Mas Suryodilogo belum mendapat perhatian yang baik dari pemerintah dan masyarakat. Program pengabdian kepada masyarakat ini bertujuan memublikasikan situs bersejarah tersebut melalui digitalisasi berupa pembuatan video dan poster infografis. PkM ini dilaksanakan pada bulan Februari hingga Juli tahun 2022 dengan menggunakan pendekatan Asset based Community Development (ABCD) yang menekankan unsur community driven. Tim pengabdi telah melaksanakan delapan tahapan yang dimulai dari pembentukan tim, training of trainers, wawancara apresiasi, pemetaan aset, observasi dan studi pustaka, FGD, pembuatan video dan poster, sosialisasi, hingga monitoring dan evaluasi. Secara umum, masyarakat menyadari bahwa mereka memiliki aset dan potensi wisata termasuk wisata religi berupa peninggalan Raden Mas Suryodilogo sehingga tim tidak menemukan kendala pada saat pemetaan aset. Masyarakat juga terlibat aktif dan bersedia untuk berpatisipasi pada saat pengambilan gambar hingga penyebaran informasi melalui output dari PkM ini.